Gorgias - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Gorgias" by Plato is a Socratic dialogue written around 380 BC. Through probing questions at a dinner gathering, Socrates challenges self-proclaimed teachers of rhetoric about the true nature of their craft. Is rhetoric an art or merely flattery? Can persuasive speech be moral without philosophy? The dialogue explores whether the power of words serves truth and justice, or simply pleasure and political advantage, as Socrates confronts the celebrated rhetoricians of Athens. (This is an automatically generated summary.)
Socrates
Wikipedia page about this book: https://en.wikipedia.org/wiki/Gorgias_(dialogue)
Release date is 1999-03-01
Sue Asscher
Keywords: Classical literature; Political science -- Early works to 1800; Ethics -- Early works to 1800